The impact of ESG performance on firm value: A comparative study of EU markets from a country and sector perspective - Sajnóg, Artur; Gawęda, Adrian (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The study aims to assess the impact of the ESG (Environmental, Social, and Governance) score of the company on its market value. The research focuses on stock companies of financial markets of European Union (EU) Member States for the years 2011–2021. The ESG discourse on the EU regulated markets was examined across nine economic sectors, in line with LSEG terminology. To test the relationship between ESG performance and firm value, the modified Ohlson Valuation Model (OVM) was utilized. Tobin’s Q was considered as the proxy of firm value, RoA as the proxy of the company’s financial performance, and ESG scoring as the proxy of ESG information that is relevant in assessing the market value. Seven control variables for firm characteristics were also included. To account for potential institutional bias, grounded in legitimacy and institutional theories, we employed two dummy variables – COUNTRY and SECTOR. The findings confirmed our research hypothesis that there is a statistically significant relationship between ESG score and firm value. In line with stakeholder theory, the results support the notion that companies with high ESG scores achieve higher firm value than those with low ESG scores, thus shedding more light on the growing importance of ESG factors for the performance of European companies. The study offers new insights into relationship between ESG performance and firm market value, examined from both from country and sectoral perspectives.